Evaluating cause-effect relationships in accident investigation using HFACS-DEMATEL - Chan, Wesley Tsz-Kin; Li, Wen-Chin; Nichanian, Arthur; Manikath, Elizabeth (Springer, 2024)
This paper addresses the ‘routes to failure’ in the causal chain of events as categorized using the Human Factors Analysis and Classification System (HFACS) framework. By using the Decision-Making Trial and Evaluation Laboratory (DEMATEL) method to evaluate the comparative influence of each HFACS category on other categories, the present research aims to classify each HFACS category as either an overall ‘cause’ or an overall ‘effect’ factor, and to give each HFACS category a comparable statistical value of their overall level of influence. Analysis of N = 30 responses from aviation safety experts identified that frontline perception faults had the potential to influence higher-level preconditions, and that ‘Environmental Factors’ were found to have the highest overall influence amongst HFACS categories at levels 1 and 2. The findings support the use of the DEMATEL method in the selection and direction of safety interventions. Safety remedies focusing on ‘cause’ factors are likely to have additional second-order benefits on associated ‘effects’, and more influential categories are likely to be more effective in influencing overall system safety. The methodology can assist safety managers in selecting and prioritizing safety initiatives, especially when faced with issues such as monetary or time constraints in the industrial context.